A Method for Analyzing Hand-Transmitted Vibration Characteristics in the Hand-Arm Parts When Operating the Portable Pneumatic Extinguisher. (7th July 2019) - Wen, Jian; Ma, Wenkai; Li, Wenbin
Abstract : This study presents the vibration transfer characteristics and the vibration absorption power distribution of the specific working condition of a portable pneumatic extinguisher. A hand-transmitted vibration biomechanical model of the hand-arm system was developed. Using a vibration test platform, the model parameters were derived simultaneously, and the driving-point mechanical impedance and distributed vibration transmissibility were measured. The vibration transmissibility of the wrist, forearm, and upper arm measured by the model was compared with the measured data of a 6MF-30 portable pneumatic extinguisher. The vibration power absorption distributions were estimated by the model and were compared with the actual vibration power absorption distributions at 3400 r/min, 5000 r/min, and 7000 r/min, respectively. The results showed that the predicted response of the model agreed well with the measured data in distribution, total impedance, and phase and can accurately fit the response curve of hand-transmitted vibration. This study discussed the vibration response of the hand-arm in the operation of the portable pneumatic extinguisher from the view of biomechanics. The analyses confirmed that the proposed model can be used as an effective tool for predicting the vibration responses of the hand-arm during the operation of a portable pneumatic extinguisher.